Synthesis and thermoelectric properties of InSb alloys by solid reaction - Wang, Kang (Data Brief, 2018)
The data presented in this article are related to the research article entitled” Synthesis and thermoelectric properties of InSb alloys by solid reaction” (Kang Wang, Peng Qin, Zhen-Hua Ge, Jing Feng ,2017) [1]. This article describes a new strategy of eutectic melting for improving the TE properties. We put the powders of In and Sb (both is 200 mesh) with a certain proportion of InSbx (x = 1.0, 1.01, 0.99, 0.97 and 0.95) and sealed them in different crucibles(23 mm × 18 mm).